PROGRESSIVE FINANCING IN INDONESIAN ISLAMIC MICROFINANCE INSTITUTIONS: IMPROVED MONITORING OR DISTINCTIVE COMMERCIALISATION? - Robbani, Muhammad Miqdad; Aulia, Mahdiah; Humaira, Fatiya Rumi (Journal of Islamic Monetary Economics and Finance, 2020)
Microfinance institutions (MFIs) play pivotal roles to providing financing and services to micro and small enterprises (MSEs) in Indonesia. Islamic MFIs, which follow Shariah principles in their operations, aim not only to provide financing, but also to improve the socioeconomic conditions of poor people. There is heightened interest in the factors influencing the development of MFIs, such as relationship lending. This study aims to explore the effectiveness of such lending and the uniqueness of the implementation of social purpose in Islamic MFIs. The paper adopts a quantitative methodology, using cross-sectional survey data from 1,001 microloan borrowers from five MFIs, three of which are Islamic MFIs which provided financing in 13 regions in Indonesia in 2018. The results show that Islamic MFIs do not differ in the implementation of relationship lending. Furthermore, there is a likelihood that they are able to be more focused on profit-oriented transactions ensuring sustainability, due to their unique characteristics, as they have Baitul Maal with the social instruments of zakat, infaq and sadaqa to provide social-oriented transactions to improve outreach to the poor. The study enhances our understanding and adds knowledge to the existing literature on Islamic MFIs, especially in Indonesia.